(untitled) (International journal of artificial intelligence, 2025)
The article presents the results of diagnostics and treatment of 84 patients with focal lesions of the prostate gland. Based on the conducted comprehensive ultrasound examination of patients, the authors determine the main specific diagnostic criteria, the use of which allows detecting prostate cancer at early stages.